Molybdenum effect on the kinetic behavior of a metal hydride electrode - Diaz, Veronica (2013)
In the present investigation, the effect of the Mo in the LaNi3,6Co0,7Mn(0.4−x)Al0,3Mox AB5-type hydrogen storage alloys was studied. The alloys structural and microstructural characterizations were performed by means of X-ray diffraction phase analysis and scanning electron microscopy. The electrochemical properties were studied through the measurements of discharge capacity, activation process, rate capability and electrochemical impedance spectroscopy of the electrodes. The replacement of manganese by molybdenum, in the intermediate concentration tested (2% w/w) has a positive effect. This alloy presents the greatest discharge capacity, the closest potential to system equilibrium potential and therefore the lowest overpotentials. This alloy also has the best behavior for high-rate dischargeability and in concordance, the lowest charge transfer resistance. This improvement is thought to be due to an increase in the active area.